A climatically significant abiotic mechanism driving carbon loss and nitrogen limitation in peat bogs - Alexandra B. Cory; Rachel M. Wilson; M. Elizabeth Holmes; William J. Riley; Yueh-Fen Li; Malak M. Tfaily; Sarah C. Bagby; Isogenie Field Team; EMERGE Project Coordinators; Patrick M. Crill; Jessica G. Ernakovich; Virginia I. Rich; et al. (Scientific Reports)
Abstract Sphagnum-dominated bogs are climatically impactful systems that exhibit two puzzling characteristics: CO2:CH4 ratios are greater than those predicted by electron balance models and C decomposition rates are enigmatically slow. We hypothesized that Maillard reactions partially explain both phenomena by increasing apparent CO2 production via eliminative decarboxylation and sequestering bioavailable nitrogen (N). We tested this hypothesis using incubations of sterilized Maillard reactants, and live and sterilized bog peat. Consistent with our hypotheses, CO2 production in the sterilized peat was equivalent to 8–13% of CO2 production in unsterilized peat, and the increased formation of aromatic N compounds decreased N-availability. Numerous sterility assessments rule out biological contamination or extracellular enzyme activity as significant sources of this CO2. These findings suggest a need for a reevaluation of the fixed CO2:CH4 production ratios commonly used in wetland biogeochemical models, which could be improved by incorporating abiotic sources of CO2 production and N sequestration.